A survey of the Sumatran Ctenidae (Araneae). 4. A new species of Acantheis Thorell, 1891 with unique copulatory organs morphology - Fomichev, Alexander A.; Omelko, Mikhail M.; Marusik, Yuri M. (Zootaxa, 2024)
A new species, Acantheis kazantsevae sp. nov., is described from Sumatra Island (Indonesia) on the basis of both sexes. The male of the new species possesses unusual palp with a twisted tegular apophysis having two arms: a large boomerang-shaped anterior one and a posterior one with a deep cavity. Diagnosis, description and illustrations are provided. Systematic placement of the new species within Acantheis Thorell, 1891 is discussed.